PROtocol‐based MObilizaTION on intensive care units: stepped‐wedge, cluster‐randomized pilot study (Pro‐Motion). Issue 6 (24th May 2019) - Nydahl, Peter; Günther, Ulf; Diers, Anja; Hesse, Stephanie; Kerschensteiner, Christian; Klarmann, Silke; Borzikowsky, Christoph; Köpke, Sascha
ABSTRACT: BACKGROUND: Early mobilization of patients in intensive care units (ICUs) improves patient recovery, but implementation remains challenging. Protocols may enhance the rate of out‐of‐bed mobilizations. AIM: To evaluate the effect of implementing a protocol for early mobilization on the rate of out‐of‐bed mobilizations and other outcomes of ICU patients. STUDY DESIGN: Multicentre, stepped‐wedge, cluster‐randomized pilot study. METHODS: After a control period, five ICUs were allocated to the implementation of an inter‐professional protocol for early mobilization in a randomized, monthly order. Mobilization of ICU patients was evaluated by monthly 1‐day point prevalence surveys using the ICU Mobility Scale. The primary outcome was the percentage of patients mobilized out of bed, defined as level 3 on the ICU Mobility Scale (sitting on edge of bed) or higher. Secondary outcomes were mechanical ventilation, delirium and ICU‐ and hospital‐days, as well as unwanted safety events. RESULTS: Out‐of‐bed mobilizations increased non‐significantly from 36·2% ( n  = 55) of 152 patients during the control period to 45·8% ( n  = 55) of 120 patients during the intervention period (difference 9·6%; 95% confidence interval −2·1 to 21·3%). Of 55 mobilized patients per group, more patients were mobilized once per day during the intervention period (intervention: n  = 41 versus control: n  = 23 patients). Multiple daily mobilizations decreased (control: n  = 32 control versus intervention: n  = 14 patients). Secondary outcomes, such as days with mechanical ventilation, delirium and in ICU and hospital, did not significantly differ. Adherence to the protocol was >90%; unwanted safety events were rare. CONCLUSIONS: Implementing a protocol for early mobilization of ICU patients showed a trend towards more patients being mobilized. Without additional staff in participating ICUs, a significant increase in ICU mobilizations was not to be anticipated. More research should address whether more staff would increase the number of frequent mobilizations and if this is relevant to outcomes. RELEVANCE TO CLINICAL PRACTICE: Implementing inter‐professional protocols for mobilization is feasible and safe and may contribute to an increase of ICU patients mobilized out of bed.